Principle of Simple, Speedy, and Low-Cost Trial and The Problem of Asset Recovery in Indonesia - Nelson, Febby Mutiara; Santoso, Topo (UI Scholars Hub, 2021)
This article discusses whether simple, speedy and low-cost principles have been implemented in the criminal justice in Indonesia and the obstacles faced by the Indonesian criminal justice system, especially in terms of returning state losses due to corruption cases. The findings indicate that such principles are yet to be effectively implemented in the criminal justice system in Indonesia. Some obvious issues have emerged as an area for attention; first, that law enforcement in corruption cases takes a long time, remains complicated, and is also high-priced. Second, there are a number of obstacles confronted by the Indonesian criminal justice system, especially in terms of returning state losses due to corruption that should be able to follow the concept of justice in a simple, speedy manner and at low cost.